NAFKAH BAGI BEKAS ISTRI DALAM PERSPEKTIF KOMPILASI HUKUM ISLAM - Dahliana (Hukum Keluarga Islam IAIN LANGSA, 2018)
Cases that occur in the decision No. 341/Pdt.G/2016/MS.Sgi and decision No. 44/Pdt.G/2017/MS-Aceh judge has granted the applicant's request and dropped one raj'idivorce against the defendant. However, in both decisions the judge disagreed inconsidering the livelihood of the claimant/comparator's claim. In the decision No. 341/Pdt.G/2016/MS. The Panel of Judges only granted the reconciliation claim for livelihoodand without granting the livelihood of the Madhiyah reconciliation claim. Whereas in thedecision No. 44/Pdt.G/2017/MS-Aceh the Panel of Judges granted a claim forreconciliation of the iddah income along with the issue, kiswah, mut'ah and also grantedthe claim of reconciliation for the livelihood of madhiyah.